Participation and Governance for More Human Smart Cities - Pultrone, Gabriella (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The smartness seems to be the decisive factor that can enable the contemporary city to face a period of deep economic and social crisis, greater awareness of the scarcity of environmental resources and the increasing demand for security, health, education, technological progress. The so called ‘new urban question’ is structured around issues which are difficult to separate such as social inequalities, climate change, the right to accessibility, with respect to which the smart perspective is an opportunity that must be used by territories and cities for the construction of development strategies based on the fundamental and inseparable dimensions of sustainability (environmental, economic, social) and on a more complex transdisciplinary approach with real effects on quality of life. The same concept of smart city - initially with a pure energetic and technologic valence - has taken on a wider and more varied meaning, aimed at understanding the satisfaction of real and emerging needs, and contemplate the active involvement of the various urban actors, transforming the public institution from "provider" to "enabler", i.e. facilitator and promoter of development. Participation and governance are therefore the keywords on which to focus for a city conscious of its rich human and social capital, in which people are the real drivers of innovation and co-designers responsible for a smart city more humane and inclusive. The ongoing experiments in this direction at the European level provide interesting insights to envision desirable future scenarios not too far away